More research and better policies are essential for achieving the World Food Summit goal: Speech given at the WORLD FOOD SUMMIT: FIVE YEARS LATER in Rome, Italy, June 10-13, 2002. - Pinstrup-Andersen, Per (International Food Policy Research Institute, 2002)
The Director-General of IFPRI emphasized, in his address, a most important fact: Poverty and hunger are now the world s most serious public health problems. Since the great majority of the world s poor and malnourished people depend directly or indirectly on agriculture for their livelihoods, one might say that agriculture is letting them down. It would be more accurate, however, to say that governments around the world are letting agriculture down. In their current circumstances, the rural poor simply do not have access to enough food or income to keep them healthy and productive. Pinstrup-Andesen continues with the strong opinion that if we are to achieve the goal set by the World Food Summit, it is essential that small farmers in developing countries become more productive. But it is no use going about our business as usual while telling poor farmers they must produce more. These farmers are doing as well as they can without better technologies and better policies. And both developing and developed countries must play their part in bringing about these improvements. He insists upon the need for publicly funded agricultural research. Besides the technological tools for producing more agricultural goods, farmers also require sound and supportive public policies.